"\\frac{dx}{x(z+2a)}=\\frac{dy}{xz+2yz+2ay}=\\frac{dz}{z(z+a)}"
"\\frac{dx}{x}=\\frac{(z+2a)dz}{z(z+a)}"
"\\int\\frac{dx}{x}=\\intop\\frac{dz}{z}+\\int\\frac{adz}{z(z+a)}"
"\\frac{1}{z(z+a)}=\\frac{A}{z}+\\frac{B}{z+a}"
"A(z+a)+Bz=a"
"A+B=0"
A=1
B=-1
"\\frac{1}{z(z+a)}=\\frac{1}{z}-\\frac{1}{z+a}"
"log(x)=log(z)-a log(z+a)+ log(c_1)=log(\\frac{c_1-z^2}{z+a})"
"c_1=\\frac{x(z+a)}{z^2}"
"\\frac{dy}{xz+2yz+2ay}=\\frac{dz}{z(z+a)}"
"\\frac{(z+a)dy}{c_1-z^3+2y(z+1)^2}=\\frac{dz}{z(z+a)}"
"\\frac{dy}{dz}-\\frac{y}{z}=\\frac{c_1-z^2}{(z+a)^2}"
"y=uv"
"y'=u'v+v'y"
"v'-v\/z=0"
v=z
"\\frac{dy}{dz}=\\frac{c_1-z^2}{(z+a)^2}"
"c_1=log(z+a)+\\frac{1}{z+a}+c_2-z"
"c_2=\\frac{y}{z}-\\frac{x(z+a)}{z^2}-log(z+a)+\\frac{1}{z+a}"
For y=0.23+x(r+a)
"c_2=\\frac{0.23+x(z+a)}{z}-\\frac{x(z+a)}{z^2}-log(z+a)+\\frac{1}{z+a}"
Substituting c1 and c2 we get the integral surface:
"\\frac{2x(z+a)}{z^2}=\\frac{2}{z+a}+\\frac{0.23+x(z+a)}{z}-z"
Comments
Leave a comment